PENINGKATAN KEMAMPUAN BERHITUNG 1-10 MELALUI VIDEO ANIMASI PADA KELOMPOK A DI RA AR ROHMAH PEKUKUHAN KECAMATAN MOJOSARI KABUPATEN MOJOKERTO - Susi Maulida; Umi Kaidaro (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
This study discusses efforts to improve early numeracy skills through animated video media. This study is motivated by the low ability to count from 1-10 in children due to the lack of learning media used by teachers. This study aims to see the effectiveness of the use of animated video media in increasing the ability to count from 1-10 in group A RA Ar-Rohmah children.In the implementation of this research, it was precisely carried out in the first semester with 2 cycles, the results of the study could be obtained by looking at the observation sheets of children who increasingly showed an increase in the development of counting 1-10 seen in the first cycle of 58% while in the second cycle it reached 83%. it can be concluded that this study was successful because it achieved an increase of up to 25%. By using animated video media, children can know the concept of numbers, recognize number symbols, count objects by playing while learning in a fun atmosphere. The use of animated videos also influences the development of children's numeracy skills with the support of activities that support them, namely creative and innovative activities.